2011
DOI: 10.1111/j.1469-7998.2011.00798.x
|View full text |Cite
|
Sign up to set email alerts
|

Common dolphin morphotypes: Niche segregation or taxonomy?

Abstract: In the extensive geographical distribution of the common dolphin, several morphotypes of uncertain taxonomic status, identified by the relative length of their rostra, have been established. We investigated variation in skull morphometrics and isotopic signatures of carbon and nitrogen (d 13 C and d 15 N) in individuals from the subtropical waters of the North Atlantic Ocean, in order to assess population structure and taxonomic status. The distribution of the relative rostral lengths (RL) of individuals follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 31 publications
3
25
0
1
Order By: Relevance
“…The long‐beaked common dolphin from the Gulf of California (GC) showed the highest δ 15 N values followed by the north‐west African population (ZIII) due probably to the presence of the long‐beaked morphotype, which is present in both areas. Consistent with this, previous studies have shown that individuals with longer beaks tend to feed at higher trophic levels than animals with shorter beaks . The short‐beaked common dolphins from Areas ZI+ZII+GAL showed the third highest δ 15 N values of the populations analysed, consistent with the published TLs for the coast of Galicia.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The long‐beaked common dolphin from the Gulf of California (GC) showed the highest δ 15 N values followed by the north‐west African population (ZIII) due probably to the presence of the long‐beaked morphotype, which is present in both areas. Consistent with this, previous studies have shown that individuals with longer beaks tend to feed at higher trophic levels than animals with shorter beaks . The short‐beaked common dolphins from Areas ZI+ZII+GAL showed the third highest δ 15 N values of the populations analysed, consistent with the published TLs for the coast of Galicia.…”
Section: Discussionsupporting
confidence: 88%
“…Only adult animals were used in this study in order to avoid variability in stable isotope abundances due to ontogenic development. The physical maturity of the specimens was established as described by Pinela and co‐authors …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotypic differentiation among populations and species inhabiting coastal and offshore aquatic environments is well established, and sometimes clearly associated with adaptive differentiation (see Schluter, 2000). For the genus Delphinus, there are coastal populations worldwide that show morphological differentiation associated with longer beak length among other characteristics, although there are also some short-beaked populations found nearshore (for example, in the Mediterranean Sea), and stable isotope analysis of beach-cast specimens was used to question the distribution of longbeaked forms off North Africa (Pinella et al, 2011). However, as we confirm here, only the long-beaked coastal population off southern California and Baja California is strongly genetically differentiated (Figure 2 and Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 99%